PELATIHAN WIRAUSAHA MAKANAN KUDAPAN SEBAGAI ALTERNATIF USAHA MANDIRI UNTUK MENINGKATKAN PENDAPATAN KELUARGA MISKIN DI DAERAH PINGGIRAN KOTA - Purwanti, Sutriyati (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2011)
This Community Service Program was intended to provide knowledge and skill in terms of: 1) snack food with various materials and processing tech- nique; 2) processing various types of Snack food using basic materials of flour (rice, wheat, sticky rice), and cassava by means of various processing techniques; 3) serving and packaging Snack food in a more interesting and hygienic way and 4) appropriate pricing for the fast-food. The training program was implemented in July 2010 by involving 25 non-working housewife mothers in the area of Pringgodani sub-village of Mri- can Yogyakarta. The materials provided included: knowledge on basic concepts, types and characteristics of Indonesian Snack foods, making Snack foods using various materials of flour (rice, wheat, sticky rice) and cassava as well as serv- ing and packaging Snack food in a more interesting and hygienic way in order to be appropriate for sales, and calculating the selling price of the Snack food. Methods used in the training were lecturing, question and answer, demonstra- tion and practice. The results of the Community Service Program were: 1) the participants have knowledge on Snack food using various materials and types and process- ing techniques; 2) the participants are able to make various types of Snack food using various types of materials and techniques of processing; 3) the participant are able to serve and package Snack food in a more interesting and hygienic way, and 4) the participants are able to appropriately calculate the selling price of the Snack food. Suggestions made based on the results of the program were: 1) the need for providing fixed outlets/food shop to serve the Snack food made by housewife mothers in such a way that it could be the center for Snack food shop and the housewife group should not vend their Snack food products; 2) the training program participants need to develop variations of their Snack food products in order to cope with bored buyers in such a way that the Snack food products accepted by consumers